1999
DOI: 10.1002/etc.5620181130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the techniques for a tiered testing approach to dredged sediment assessment—a study over a metal concentration gradient

Abstract: A sediment quality triad approach was used to evaluate Environment Canada's battery of marine bioassays and the proposed pass/fail criteria along a metals gradient in Belledune Harbour, New Brunswick, Canada. Most assays performed consistently, but certain tests provided less response than expected at the more contaminated stations (amphipod survival and light reduction in photoluminescent bacteria tests passed according to proposed pass/fail criteria). Echinoid fertilization tests were quite sensitive. Bioacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Thus, if sediment COPC concentrations are below SQGs that predict minimal effects (SQG‐low), then there is likely negligible ecological risk. These observations are corroborated by Porebski et al (1999), for example, who found that such SQG‐low values nearly always represented levels below which unacceptable biological effects were unlikely to occur in sediment. Because SQGs have no role in evaluating human health risks or biomagnification (Wenning and Ingersoll 2002) and there are no such sediment guidelines, initial (conservative) decisions regarding biomagnification potential are simply based on the presence or absence of quantifiable amounts of substances that may biomagnify.…”
Section: The Sediment Decision‐making Frameworksupporting
confidence: 71%
“…Thus, if sediment COPC concentrations are below SQGs that predict minimal effects (SQG‐low), then there is likely negligible ecological risk. These observations are corroborated by Porebski et al (1999), for example, who found that such SQG‐low values nearly always represented levels below which unacceptable biological effects were unlikely to occur in sediment. Because SQGs have no role in evaluating human health risks or biomagnification (Wenning and Ingersoll 2002) and there are no such sediment guidelines, initial (conservative) decisions regarding biomagnification potential are simply based on the presence or absence of quantifiable amounts of substances that may biomagnify.…”
Section: The Sediment Decision‐making Frameworksupporting
confidence: 71%
“…Homogenized control sediment was separated into five aliquots: One 1,200‐g aliquot destined for control; another 1,200‐g aliquot for adjustment to 200 μg/g lead; and three 1,000‐g aliquots to be spiked to 50, 100, and 400 μg/g lead, respectively. This range included the ERM of 218 μg/g and effects‐range low of 47 μg/g for lead reported for other amphipods in acute 10‐d or chronic 28‐d bioassays [31,34,35]. These sediments were sealed in Nalgene® (United States Plastic Corporation, Lima, OH, USA) polymethylpen‐tane containers and stored overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of whole‐sediment toxicity assessed through bioassays and related to ecotoxicological impacts has lead to the establishment of sediment quality guidelines. These guidelines were developed to protect biological resources and humans from the effects of contaminated sediment ([6,14,16,22,26,27,30–33]; http://www.ene.gov.on.ca/envision/gp/B1-3.pdf; http://response.restoration.noaa.gov/book_shelf/121_sedi_qual_guide.pdf). Contaminant levels at or below a concentration rarely showing adverse biological effects typically are classified as either the effects‐range low or the threshold‐effects level [32–35].…”
Section: Introductionmentioning
confidence: 99%
“…Microtox has been incorporated into both informal and traditional triad designs in a limited number of studies. For instance, Porebski et al (1999) used a combination of bioassays that included Microtox pore water and solid-phase tests, sample chemistry and benthic community structure to assess pollution along a gradient in Belledune Harbour, New Brunswick. A similar approach had been adopted earlier by Day et al (1995).…”
Section: Trifolium Pratensementioning
confidence: 99%